Teaching Writing from a Writer's Point of View Terry Hermsen, Ed. and Robert Fox, Ed. - Hermsen, Terry; Fox, Robert (Distributed by ERIC Clearinghouse, 1998)
Based on a series of successful summer writing institutes, this book presents practical ways for teachers to reinvigorate their classrooms and their own attitudes toward creative writing. In four complementary sections focusing on four groups of writers--creative writers in residence, K-12 students and teachers who participated in the summer institutes, and established writers such as Ron Carlson and Scott Russell Sanders--the book demonstrates the enormous variety and high quality of writing that result when people use writing to discover what they want to say. After an introduction by Robert Fox ("The Experience of Writing: A Summer Institute"), the first section presents essays by Ohio writers in the schools; "Doing Our Own Possibility: Journal of a Residency at Columbiana County Head Start Centers" (Debra Conner); "Playwriting: A Teaching Approach Using the Stories of Our Lives" (Michael McGee London); "Just across the Street: The Story of a Teacher-Based Residency" (Lynn Powell); "Translytics: Creative Writing Derived from Foreign Language Texts" (Nick Muska); "How to Do a Poetry Night Hike" (Terry Hermsen); and "Reading to a Sky of Soba" (David Hassler). The second part presents poems, stories, and plays from 13 Ohio schools. The third part presents essays from participants in the experience of writing: "When Spirit Moves, Children Sing" (MaryAnn Titus); "Sudden Revelation: Fiction Writing in the Classroom" (Carl H. Krauskopf III); "A Year of Writing Workshop" (Mary L. Noble); "Word Works: Building a Community of Writers" (Janice M. Gallagher); and"Green Digits and Colons: Find Time to Write" (Barry Peters). The last section presents essays from experiences of writing faculty: "Turning the Desk" (Ron Carlson); "The Singular First Person" (Scott Russell Sanders); and "Reveling in the World: An Interview with Christopher Merrill on the Power of Language and Teaching" (Terry Hermsen). (RS)
ERIC Document Number: ED422582.
Availability: National Council of Teachers of English, 1111 W. Kenyon Road, Urbana, IL 61801-1096 (Stock No. 55170-3050: $16.95 members, $22.95 nonmembers).
ERIC Note: Based on a summer writing seminar cosponsored by Wright State University and Ohio Arts Council.
Keywords: Class Activities.; Creative Writing.; Elementary Secondary Education.; Summer Programs.; Writing Attitudes.; Writing Instruction.; Writing Workshops.